Boosting of water splitting using the chemical energy simultaneously harvested from light, kinetic energy and electrical energy using N doped 4H-SiC nanohole arrays. (15th December 2022) - Zhou, Linlin; Yang, Tao; Fang, Zhi; Zhou, Jiadong; Zheng, Yapeng; Guo, Chunyu; Zhu, Laipan; Wang, Enhui; Hou, Xinmei; Chou, Kuo-Chih; Wang, Zhong Lin
Abstract: Piezoelectric polarization promoted photoelectrochemical (PE-PEC) water splitting is a promising strategy to obtain hydrogen energy by converting light, kinetic, and electrical energy into chemical energy. However, novel piezoelectric semiconductors are urgently needed owing to the improper band positions and poor stability of most current piezoelectric materials. In this work, a method of inducing piezopotential in N doped 4H-SiC nanohole arrays (NHAs) for water splitting is proposed. The modulation effects of N doping with various contents on the electronic structure and piezoelectricity of 4H-SiC are comprehensively analyzed. By introducing piezoelectric field to regulate transport behavior of charges, the current density of NHAs reaches 6.50 mA cm −2 at 1.4 VAg/AgCl, indicating a 50.1% enhancement compared with that without polarization (4.33 mA cm −2 at 1.4 VAg/AgCl ). The conjunction mechanism of photoelectric catalytic capacity and piezoelectricity of N doped 4H-SiC NHAs is elaborated, providing powerful guidance for manufacturing piezoelectric semiconductor photoanodes in PE-PEC water splitting. Graphical Abstract: The exploration of tri-harvesting light, kinetic, and electrical energy for efficient water splitting using N doped 4H-SiC nanohole arrays (NHAs) is reported for the first time. The mechanism of simultaneously optimizing electronic structure and enhancing piezoelectricity of 4H-SiC by N doping is demonstrated. By introducing a piezoelectric field to regulate the transport behavior of charges, the current density of NHAs reaches 6.50 mA cm −2 at 1.4 VAg/AgCl, indicating a 50.1% enhancement compared with that without polarization (4.33 mA cm −2 at 1.4 VAg/AgCl ). This provides powerful guidance for manufacturing piezoelectric semiconductor photoanodes in water splitting. ga1 Highlights: N doped 4H-SiC nanohole arrays are capable of tri-harvesting light, kinetic and electrical energy for water splitting. The mechanism of optimizing electronic structure and enhancing piezoelectricity of 4H-SiC by N doping is demonstrated. Piezoelectric polarization promoted photoelectrochemical water splitting based on N doped 4H-SiC NHAs is feasible.